Occupational adjustment and its relationship to organizational loyalty among the workers of the Sonelgaz Corporation in Laghouat - a field study - - - REIACHE, Said; NAKMOUCHE, Mohamed Tahar (Social Sciences Journal)
This study aimed to identify the relationship between the professional compatibility and organizational loyalty in selected groups of workers at Sonelgaz company inLaghouat city, , also aimed to find out the differences in professional compatibility in light of theintermediate variables (social status, socio-professionalclass, and the service duration) . The Descriptive method of research has beenfollowed in this studythat fits with the nature of the subject on a sample of (96) worker, who have been selected in a random sample, also this study used two Criteriaare the compatibility professional Criterion, of Abdullah Abdul Aziz Samari (2010), and the organizational loyalty Criterion by the student researcher, so a number of various methods has been used in the statistical processing (the average, standard deviation, the Pearson correlation coefficient, Guttman correlation coefficient, Cronbach’s alpha coefficient, analysis of variance, T test, and then applying the SPSS17 for the statistical analysis).The results of the study concluded: There is a positive relationship between positive compatibility professional and organizational loyalty at Sonelgaz,There are no statistically significant differences among Sonelgaz workers in vocational compatibility attributed in light of (social status, socio-professionalclass, and the service duration)